Spectral Reflectance of Powder Coatings on Carbonaceous Chondrite Slabs: Implications for Asteroid Regolith Observations. Issue 10 (30th October 2018) - Kiddell, C. B.; Cloutis, E. A.; Dagdick, B. R.; Stromberg, J. M.; Applin, D. M.; Mann, J. P.
Abstract: Carbonaceous chondrite meteorites (CCs) are among the most primitive materials in the solar system and provide important insights into solar system history and evolution. A number of planetary spacecraft missions will visit asteroids that are thought to compositionally resemble these meteorites. To better assist sample acquisition in terms of how the physical properties of CCs affect their reflectance spectra, we investigated the spectral reflectance properties of solid and powdered CCs and powder coatings on slabs of a number of CCs, including CB, CH, CK, CM, CO, CR, and CV classes. We found that decreasing grain size leads to increasing reflectance across the 500‐ to 2, 500‐nm range and steeper spectral slope, regardless of CC type. Powdered CC reflectance spectra are brighter beyond 500 nm and redder than bare roughened slabs. For powders sprinkled on slabs, as the powder coating gets thicker, spectral slopes get redder. Optically thick fine‐grained powders are brighter beyond 500 nm and are as red or redder than slabs covered with airfall dust (for dust thicknesses up to a few hundred microns). Diagnostic absorption features of CC minerals, particularly those in the 1, 000‐nm region attributable to Fe‐bearing silicates, are ubiquitous regardless of physical properties. Reflectance spectra of terrestrially weathered (i.e., rusty ) CCs are strongly modified below 700 nm and in the 900‐ and 1, 900‐nm regions by these Fe oxyhydroxides. Their effects can be mitigated through chemical treatment, but this may also affect preterrestrial ferric iron‐bearing phases. Some spectral characteristics, such as hydrous and anhydrous silicate absorption bands in CC spectra, are present regardless of physical properties (fine‐grained dust, powders, slabs, and dust on slabs). Other spectral characteristics (such as albedo and spectral slope) vary as a function of physical properties, indicating that reflectance spectroscopy could be used to ascribe spectral variations across an asteroid's surface to either physical or compositional causes. This information can, in turn, be used to inform site selection for asteroid sample return missions, where both composition and physical properties are important drivers. When searching for fine‐grained areas on an asteroid to sample, the best indication would be the brightest‐ and reddest‐sloped spectra. Plain Language Summary: Carbonaceous chondrites are a group of meteorites that are important for understanding the evolution of life on Earth because they contain various organic compounds that may have seeded the Earth with the essential building blocks of life. Because of their scientific importance, a number of planetary spacecraft missions will visit asteroids that are thought to be the sources of these meteorites. Primarily to assist these asteroid sample return missions to successfully acquire a sample to bring back to the Earth, we have studied how spectrometers on board these spacecraft may be able to distinguish regions that can be sampled from those that cannot (each mission has unique needs in terms of the kinds of surfaces they can best sample). Specifically, we looked at how solid surfaces can be distinguished from powdered and rubbly surfaces. We found that different kinds of surfaces can be distinguished by how they reflect sunlight, in terms of properties such as brightness, how brightness changes at different wavelengths, and how the intensity of mineral‐specific absorption bands vary. Key Points: Spectral reflectance of various grain size fractions (<5‐1, 000 micrometers) of carbonaceous chondrites was measured and analyzed Spectral reflectance of carbonaceous chondrite dust coatings of variable thickness on carbonaceous chondrite slabs was measured These empirical measurements will be useful for studying the compositional and physical properties of asteroids Bennu and Ryugu